Random vector variational inequalities and random noncooperative vector equilibrium. (1997) - Lee, Gue Myung; Lee, Byung Soo; Chang, Shih-Sen
Abstract : In this paper, we prove some existence theorems for random vector variational inequalities and an existence theorem for the random noncooperative vector equilibrium under suitable assumptions.